2021
DOI: 10.1126/sciadv.abj2946
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Atlantification along the Fram Strait at the beginning of the 20th century

Abstract: Subpolar Atlantic dynamics drive Arctic climate at the onset of the 20th century.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 88 publications
2
47
0
Order By: Relevance
“…OHC changes in the Arctic Ocean are strongly affected by rapid environmental changes, ocean heat transport and local air-sea/ice-sea heat exchanges 20,194 . For instance, ocean warming can be directly affected by heat transport into the region associated with the rapid decline of sea ice and the concurrent expansion of Atlantic waters into the Arctic Ocean (' Atlantification') [196][197][198][199] . However, direct observations reveal no significant trend in heat transport from the subtropical North Atlantic to the Arctic from 2014 to 2018 119,200 , although others suggest an increase from 1993 to 2016 201 , highlighting disparities related to both data uncertainty and substantial interannual variability 20 .…”
Section: Global Deep and Full-depth Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…OHC changes in the Arctic Ocean are strongly affected by rapid environmental changes, ocean heat transport and local air-sea/ice-sea heat exchanges 20,194 . For instance, ocean warming can be directly affected by heat transport into the region associated with the rapid decline of sea ice and the concurrent expansion of Atlantic waters into the Arctic Ocean (' Atlantification') [196][197][198][199] . However, direct observations reveal no significant trend in heat transport from the subtropical North Atlantic to the Arctic from 2014 to 2018 119,200 , although others suggest an increase from 1993 to 2016 201 , highlighting disparities related to both data uncertainty and substantial interannual variability 20 .…”
Section: Global Deep and Full-depth Changesmentioning
confidence: 99%
“…However, direct observations reveal no significant trend in heat transport from the subtropical North Atlantic to the Arctic from 2014 to 2018 119,200 , although others suggest an increase from 1993 to 2016 201 , highlighting disparities related to both data uncertainty and substantial interannual variability 20 . Other environmental changes also affect Arctic Ocean OHC, including amplified surface warming since the 1960s at a rate twice the global value, driven by positive surface heat flux into the ocean associated with reduced outgoing longwave radiation and a reduction in albedo from the sea-ice-albedo feedback 23,197 . However, the air-sea/ice-sea heat exchanges are currently poorly quantified because of the data insufficiency 20 .…”
Section: Global Deep and Full-depth Changesmentioning
confidence: 99%
“…It is unclear if this phenomenon of Atlantification in the eastern Eurasian Basin represents a typical trend under climate change, or a decadal variability that was possibly enhanced by climate change. At least the analysis of paleoceanographic records has indicated that the aforementioned ocean warming in the Fram Strait in the early 21st century is unprecedented for the past 800 years (Tesi et al, 2021).…”
Section: Atlantic Water Layer In the Arctic Oceanmentioning
confidence: 99%
“…The analysis and findings of this work also can be applied to investigate the dynamics of the Arctic Ocean. The Arctic Ocean is undergoing a so-called Atlantification, in which the area of warm and saline Atlantic Water is gradually expanding (AsbjĂžrnsen et al, 2020;Tesi et al, 2021). The summer ice in the Arctic is rapidly decreasing (Perovich et al, 2019), and potential future scenarios from climate models project an ice-free interior Arctic by around 2050 (Collins et al, 2013).…”
Section: Linking the Nordic Seas And The Arctic Oceanmentioning
confidence: 99%